Plant molecular biology labfax - Croy, R. R. D. (Labfax series., 1993)
LABFAX volumes are purpose-designed data reference books for practicing scientists. Each book presents key information for a major subject in one place and so saves hours of searching. It does not simply collect together data which are already available in catalogs, since these are often incomplete and can contain conflicting information. Rather, the authors and editors of each LABFAX volume have searched the original literature for the accurate data which they know the specialist needs. Plant Molecular Biology Labfax is a detailed compendium of essential information on plant nucleic acids, transformation and expression vectors, selectable genes and reporter genes, gene expression and PCR techniques, etc. A key feature is the Plant Gene Index, comprising comprehensive tables of plant genes published and submitted to sequence databases. Plant Molecular Biology Labfax, while specializing in molecular aspects of plant science, inevitably has numerous sections dealing with general molecular biology which complement the extensive information provided in Molecular Biology Labfax. It is therefore a worthy companion to this text.